Slayer - Karen Koehler
His name is Alek Knight. He is tall and beautiful...and a master assassin. His raven black hair is worn long to symbolize his status in the Coven, his cult of Vatican-trained, vampire-slaying allies. He is a master swordsman, a prodigy even among ancients. And for good reason: he is one of the rare and deadly dhampiri--an evolved form of the creature we know of today as Vampire. Alek possesses an almost supernatural talent for slaying vampires and his weapon of choice is the legendary Double Serpent Katana, an ancient sword forged by master swordsman Hattori Hanzo for the Japanese Ninja class over 400 years ago.